Antitumor activity of rucaparib plus PLX038A in serous endometrial carcinoma - Xiaonan Hou; Valentina Zanfagnin; Conway Xu; Erik Jessen; Yuanhang Liu; Chen Wang; Yajue Huang; Shaun D. Fontaine; Daniel V. Santi; Gerardo Colon-Otero; Sarah E. Gill; Gretchen E. Glaser; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Serous endometrial cancer (SEC) is a genomically and morphologically distinct endometrial cancer (EC) subtype with a poor progression-free and overall survival. The development of novel therapies is needed to improve outcomes. Methods We used serous and serous-like EC patient-derived xenografts (PDXs) to test a novel drug combination in vitro and in vivo: rucaparib and pegylated SN-38 (PLX038A). Sensitivity to treatment was correlated with indicators of homologous recombination (HR) deficiency. Efficacy in fresh primary patient tumors was also tested ex vivo. Results Five of eight PDXs had genomic instability scores ≥ 42, but only one of these five had evidence of HR deficiency in assays of irradiation-induced RAD51 foci formation. Moreover, PARP inhibitor (PARPi) monotherapy failed to induce regressions in any of the five SEC models treated with rucaparib in vivo, suggesting limited clinical activity of PARPi in SEC. In further studies, we assessed the response of these models to the sustained release topoisomerase 1 inhibitor, PLX038A, as monotherapy and in combination with rucaparib ex vivo and in vivo. Results of these studies showed that PLX038A had limited monotherapy activity, but combination therapy induced significant regressions in two of five SEC PDXs and markedly slowed tumor growth in the other three regardless of underlying homologous recombination repair deficiency. In addition, 11 of 20 (55%) primary tumors showed synergy with rucaparib + SN-38. Conclusions Collectively, these studies identify a set of genomically characterized PDX models for preclinical testing of potential SEC therapies and a therapeutic combination that warrants further preclinical investigation.